Effect of a preventive strategic control program, with imidocarb dipropionate, against tick fever agents in dairy calves - Alves, Histefania Costa; Afonso, Pedro Henrique Amancio; Salvador, Vanessa Ferreira; Leal, Luccas Lourenzo Lima Lins; de Morais, Igor Maciel Lopes; Ferreira, Lorena Lopes; de Aquino, Lídia Mendes; Couto, Luiz Fellipe Monteiro; Heller, Luciana Maffini; Zapa, Dina Maria Beltran; Cruz, Breno Cayeiro [UNESP]; Soares, Vando Edésio; et al. (Springer Nature, 2023)
Chemoprophylaxis with dipropionate imidocarb (IMD) is a method adopted to prevent cattle tick fever (TF). Sixty weaned dairy heifers (±60 days old), without previous exposure to Rhipicephalus microplus ticks, were housed in Tifton paddocks and were subsequently exposed to R. microplus ticks and monitored up to 315 days old. Thirty animals were kept as controls (T01) and 30 received five preventive strategic treatments with IMD at 21-day intervals (T02). The heifers were monitored weekly by means of packed cell volume (PCV) and blood smears to evaluate the presence of TF agents. Salvage treatments (ST) with diminazene and enrofloxacin were administered when animals showed PCV ≤ 24%. The A. marginale prevalence was 39.3% and 37.7%, B. bovis 6.0%, and 7.3%, and B. bigemina 16.3% and 13.7% for T01 and T02, respectively. Regarding PCV values, group T01 showed lower PCV than group T02, between 119 and 161 days of life, but when animals were 196, 210, 217, and between 252 to 301 days old, an inversion occurred. The IMD treatment protocol was effective in group T02 from day 91 to 175 while treatment was being administered, but from day 182 to 315 after the IMD treatment protocol was completed, the number of salvage treatments against TF agents performed in T02 group increased significantly. The sequential application of IMD treatments with intervals less than 21 days is not recommended.
Keywords: Anaplasmosis; Babesiosis; Chemoprophylaxis; Packed cell volume; Tick-borne diseases